Lynas Advanced Materials Plant - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Dzulkefli, Najwa Anis (Management Centre, IIUM, 2011)
This case study illustrates the issues regarding Lynas Advanced Material Plant. The Lynas Corporation Ltd of Australia first looked at China before settling on Pahang, Malaysia to establish its rare earth processing plant. Rare earth is a slightly radioactive material. Despite reassurances by the company and the State and Federal governments that the Lynas Advanced Material Plant is not dangerous to the employees and the community, some NGOs and the public are still skeptical. They say the benefits derived from investment may not outweigh the risks. The case presents a balanced perspective on both the benefits and risks of this project.